Evaluation of Multifunction Bioactivities of Extracted Chitosan and their UV/Ozone Derivatives - Tamer I. M. Ragab, Gehan T. El-Bassyouni, Wafaa A. Helmy, Hanan A. A. Taie, Ahmed Refaat, Medhat A. Ibrahim, Eman Abd El-Hmeed, Mona A. Esawy (Journal of Applied Pharmaceutical Science, 2018)
The objective of the present study was the extraction of chitosan from the seashell exoskeleton, then it was modified by the exposure to different time intervals of ultraviolet/ozone (UV/ozone). Also, the study focused on the differentiation between the properties of native chitosan and their UV/ozone forms. The molecular weight and degree of deacetylation of the extracted chitosan were determined. UV/ozone modified chitosan was analyzed using FTIR. The result proved that the irradiation of the prepared samples resulted in slight shifts in the absorbance bands position, also the occurrence of UV-induced photooxidation in the range of OH vibration. Molecular modeling at B3LYP/6-31g(d, p) and PM6 levels indicated that radiation was supposed to affect the H-bonding of the NH2 group through weak interaction with the six-respective hydrogen bonding in the three NH2 groups. UV/ozone chitosan acquired improvement in the antimicrobial activity by an increment of the exposure time against different pathogen with variable degrees. Antioxidant activity was determined using different methods and the results confirmed the role of UV/ozone in improving this property. The fibrinolytic activity reported that chitosan treated with UV/ozone for 3 and 4 h showed great activity. On the other hand, the anticoagulant activity was non-significant.
Keywords: Chitosan, UV/ozone, Molecular modeling, antimicrobial, anticoagulant and fibrinolytic activity.